Vitamin D and LL-37 in cirrhotic patients with culture-positive spontaneous bacterial peritonitis - Ahmed El Sayed Zeid; Perihan El Sayed Salem; Abeer S El Hadidi; Tamim G Ibrahim (SpringerOpen, 2019)
Background and aims Spontaneous bacterial peritonitis (SBP) is a common bacterial infection in patients with liver cirrhosis and ascites. Cirrhotic patients frequently have vitamin D (Vit-D) deficiency. Vit-D induces the production of LL-37, an important molecule of innate immunity, in macrophages. The aim of this study is to assess Vit-D and LL-37 levels in the ascitic fluid (AF) of cirrhotic patients with SBP in comparison to patients with simple ascites. Patients and methods Forty male cirrhotic patients with ascites were included and were divided into two groups, 20 with culture-positive SBP (group I) and 20 with simple ascites (group II). AF Vit-D and LL-37 levels were measured. Results Vit-D and LL-37 levels were significantly lower in patients with SBP than those with simple ascites. In univariate analysis, the risk factors for SBP were lower platelet count, higher leukocytic count, higher serum bilirubin, lower prothrombin activity, lower serum albumin, higher Child-Pugh and model for end-stage liver diseases scores, and lower AF Vit-D and LL-37 levels, while in multivariate analysis, a lower AF Vit-D level was the only risk factor for SBP. Conclusion Patients with SBP have lower levels of AF Vit-D and LL-37 than simple ascites, where an inadequate expression of LL-37 in AF due to the low Vit-D level may increase the susceptibility to SBP.